Efficacy and safety of baihe gujin decoction as an adjunct to chemotherapy in pulmonary tuberculosis: A systematic review and meta-analysis - Zhao, Yilu; Han, Yiran; Liu, Jia; Niu, Honghong; Wang, Peilong; Li, Yuxi; Liang, Jianqin; Gong, Wenping (Frontiers in Pharmacology, 2025)
BackgroundPulmonary tuberculosis (PTB), an ancient affliction, continues to present significant challenges in modern medicine. Baihe Gujin Decoction, a traditional Chinese botanical drug remedy, has been widely utilized in clinical practice for tuberculosis treatment, yet its efficacy has been inconsistent. This meta-analysis aims to ascertain its effectiveness and contribute to evidence-based medicine.MethodsA comprehensive search was conducted across multiple databases, including PubMed, Embase, The Cochrane Library, China Science and Technology Journal Database, Wanfang Database, China Biomedical Literature Database, and China National Knowledge Infrastructure, to identify relevant randomized controlled trials from January 2010 to February 2024. The risk of bias in the included studies was assessed using the Cochrane Collaboration’s tool, and meta-analyses were performed using Review Manager and Stata to evaluate the comparative outcomes.ResultsThis meta-analysis encompassed 32 studies. The control group exhibited a notably higher clinical overall efficacy rate [OR = 5.50, 95%CI (4.18, 7.24), P < 0.05], lesion absorption rate [OR = 5.83, 95%CI (4.08, 8.33), P < 0.05], cavity change rate [OR = 2.35, 95%CI (1.50, 3.69), P < 0.05], and sputum negative conversion rate [OR = 2.85, 95%CI (2.12, 3.83), P < 0.05]. In contrast, the treatment group demonstrated an increase in CD4+ T lymphocyte subset levels post-treatment, with a weighted mean difference of [OR = 4.87, (95%CI (1.91, 7.83), P < 0.05]. Furthermore, safety indices, including the incidence of total adverse reactions, liver function abnormalities, and gastrointestinal reactions, were significantly lower in the treatment group.ConclusionThe combination of Baihe Gujin Decoction with biomedicine is more efficacious than biomedicine alone for treating PTB. This superiority is evident in improved clinical efficacy rates, lesion absorption, cavity changes, sputum negative conversion rates, and immune indices, alongside a reduced incidence of adverse reactions.Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/, CRD42023462056